2018
DOI: 10.21859/ajcm.25.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Potential Drug Interactions and Related Factors in Patients Admitted in Department of Cardiology of Farshchian Heart Hospital of Hamadan

Abstract: Background and Objective: Cardiovascular patients are susceptible to drug interactions due to the simultaneous use of several drug types. The purpose of this descriptive-analytic study was to evaluate the potential drug interactions and the related factors in subjects admitted to the Cardiology Department of Farshchian heart hospital of Hamadan, Iran. Materials and Methods: This descriptive cross-sectional study was conducted on 900 subjects. The data, including drugs, sex, type of illness, and length of hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In the present study, drug interactions in none of the hospitals were significantly different between women and men and were almost the same between women and men. According to Turkashund et al 15 study, the prevalence of interference was higher in women than in men. Some studies show no difference between the two sexes 20 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the present study, drug interactions in none of the hospitals were significantly different between women and men and were almost the same between women and men. According to Turkashund et al 15 study, the prevalence of interference was higher in women than in men. Some studies show no difference between the two sexes 20 .…”
Section: Discussionmentioning
confidence: 91%
“…In Turkashund et al 15 study, out of 4318 interference cases, 2708 (62.7%) were related to moderate interferences and 1610 (37.3%) of those were severe interferences of replacement therapy. In the studies conducted in Pakistan 16 and India 13 also reported the most cases of drug interaction intensity at a medium level.…”
Section: Discussionmentioning
confidence: 92%